The Fate of Nitrogen Applied to Florida Turfgrass - Travis W. Shaddox; Joseph Bryan Unruh (EDIS)
The quality of Florida’s surface and ground waters is of utmost importance to the flora and fauna living in them, as their growth is directly related to the amount of nutrients in these waters. In order to make informed decisions regarding nitrogen (N) applications to turfgrass, it is important to understand the N cycle in the soil/turfgrass system. The objective of this 8-page publication is to identify and describe the sources and potential fates of N applied to Florida turfgrass. Written by T.W. Shaddox and J.B. Unruh and published by the UF/IFAS Department of Environmental Horticulture, January 2018. http://edis.ifas.ufl.edu/ep546